IMPACT OF WORK INTERFERENCE WITH FAMILY ON EMPLOYEE WELLBEING: A STUDY OF REMOTE WORKERS IN THE IT BASED ORGANIZATIONS - MODERATING EFFECT SOCIAL ISOLATION - Randika, L.B.Y.; Wijewantha, P. (Department of Human Resource Management, Faculty of Commerce and Management Studies, University of Kelaniya, Sri Lanka., 2025)
The aim of this research will revolve around analyzing the impact of work interference with family (WIF) on the wellbeing of employees and the moderation of social isolation among remote workers in IT-based organizations in Sri Lanka. Based on Work-Family Conflict Theory and Conservation of Resources Theory, the approach used in this study was quantitative. Accordingly, data collection was from 182 executive-level employees who responded to a self-administered questionnaire. These results showed that there was a significant negative relation between work interfering with family and the employee well-being, (β = -.751, p 0.90.) These findings extend the extant literature by demonstrating heightened effects of work – family conflict in remote settings and identifying social isolation as a critical boundary condition. The present research has several implications for organizations managing remote employees, in particular in extending considerable policies for boundary management and creating ways for encouraging social connectivity.
Keywords: Employee Well-being; IT Organizations; Remote Work; Social Isolation; Sri Lanka